Reaksi Signal Faktor Makroekonomi, Fundamental, dan Resiko Sistemis (Beta Saham) Terhadap Return Saham Syariah yang Terdaftar di Jakarta Islamic Index (JII) - Purboyo Purboyo; Rizka Zulfikar (At-Tadbir : jurnal ilmiah manajemen, 2017)
This study aims to determine the effect of macroeconomic factors, corporate fundamentals and systemic risk on the return of Sharia shares in Indonesia stock exchanges incorporated in Jakarta Islamic Index (JII) shares during the period of 2013-2016. By using purposive sampling method, obtained 11 sharia-compliant company which for four years or eight times in a row enter into index JII. The variables studied consist of GDP, Inflation, DER, ROA, Beta (systemic risk) and stock return. Hypotheses test method was using multiple regression analysis by SPSS, the result of statistical test F test (F-test) indicate the result that all independent variables (GDP, inflation, DER, ROA, BETA) simultaneously have significant effect to stock return by the significance level of 0,002 , the result of statistical test with  t-test indicate that there are two variables that is inflation with significance level 0,017 and DER with significance level 0,030 have significant effect to return of syariah stock, while other variable that is GDP, ROA and BETA have no significant effect to stock return sharia. Keywords: Sharia stock, GDP, Inflation, Corporate fundamentals, systemic risk, Stock returns